Kepemimpinan Berbasis Pelayanan Dan Implikasinya terhadap Disiplin Guru: Studi Kuantitatif Di SMA Pertiwi 1 Padang (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to analyze the effect of service-based leadership on teacher discipline at SMA Pertiwi 1 Padang. The study used a quantitative approach, with survey methods and questionnaire instruments. The population and sample consisted of 38 teachers of SMA Pertiwi 1 Padang. Data collection using a questionnaire, then statistically analyzed using simple linear regression. The results showed that service-based leadership has a significant influence on teacher discipline. This is evidenced by the regression coefficient (β) which is positive and significant (p < 0.05). In other words, the more service-based leadership is implemented, the more teacher discipline increases. This study provides important implications, namely school principals are advised to continue developing service-based leadership in order to create maximum work discipline among teachers.